Arbuscular mycorrhizal fungi mitigates heavy metal toxicity adverse effects in sewage water contaminated soil on Tagetes erecta L. Issue 5 (3rd September 2018) - Elhindi, Khalid M.; Al-Mana, Fahad A.; El-Hendawy, Salah; Al-Selwey, Wadei A.; Elgorban, Abdallah M.
ABSTRACT: The aim of this experiment was to evaluate the impact of colonization with arbuscular mycorrhizal (AM) fungus Glomus constrictum on the biomass production, flower quality, chlorophyll content, macronutrients and heavy metals content of marigold ( Tagetes erecta L.) planted under uncontaminated soil and watered with various rates of sewage water. Sewage water utilization significantly decreased biomass production, characters of flower, nutrient concentration and rates of mycorrhizal colonization of mycorrhizal (M) and non-mycorrhizal (NM) marigold as compared to control untreated plants especially at the higher rates, but the reduction rate was proportionally higher in non-AM treatments. Mycorrhizal plants had significantly greater yield, relative chlorophyll content, leaf area, flower quality and element (P, N, K and Mg) content compared to non-inoculated marigold plants irrigated with or without sewage water. Furthermore, AM inoculation had highly decreased heavy metal (Zn, Co, Mn, Cu) content in tissues as compared to equivalent non-inoculated plants grown under sewage water application. Growing marigold with AM inoculum can reduce toxicity of heavy metals and enhance biomass production and P uptake. The results support the view that AM have a protective function for the host plant, hence playing a potential function in soil polluted immobilization processes, and thus are of assessing the potential of phytoremediation of heavy metals in sewage water contaminated soil.